EFFECTS OF NATURAL HONEY ON BLOOD GLUCOSE AND LIPID PROFILE IN YOUNG HEALTHY PAKISTANI MALES - Majid, Muhammad; Younis, M. Azeem; Naveed, Abdul Khaliq; Shah, Muhammad Usman; Azeem, Zahid; Tirmizi, Syed Haider (Journal of Ayub Medical College Abbottabad, 2014)
Technology, Rawalpindi, Pakistan Background: Honey has been shown to have beneficial effects on glucose and lipid profiles in patients at high risk of heart diseases. Therefore, this study was carried out to investigate the effects of natural honey on blood glucose and lipid profile in healthy individuals. Methods: A randomized controlled trial was carried out in the Army Medical College, Rawalpindi, Pakistan, spanning 4 weeks, that is, from 15th February to 15th March 2009. A total of 70 healthy young boarders of the same college were included in the study and randomly divided into two groups of 35 each using random number table. Seventy gram (70g) of honey was given to each individual in the experimental group daily for a period of 4 weeks while control group was kept on the same diet as that of experimental group except honey. The fasting glucose, total cholesterol, low density lipoprotein (LDL), high density lipoprotein (HDL) and triglyceride (TG) levels were measured before and after the experiment. Results: Fasting glucose levels in both groups were raised. However, the increase in the experimental group was significantly less than that in the control group (p<0.05). The levels of total cholesterol, LDL and triglycerides in the control group increased while those in the experiment group decreased significantly (p<0.05), while HDL levels were decreased in the former and increased in the latter group (p<0.05). Conclusion: Natural honey consumption significantly limits the rise in blood glucose along with a significant decrease in the levels of total cholesterol, LDL and triglycerides, and increase HDL in young healthy adults. Keywords: Honey, Glucose profile, Lipid profile